DID UN PROMOTE THE RIGHT TO SELFDETERMINATION TO THE PEOPLE IN EAST TIMOR? - Ongge, Omi (European Scientific Journal, ESJ, 2015)
Started 1998, Indonesia faced political instability due to the social unrest and the step down of Indonesian President Soeharto. The condition impacted into the East Timor condition to have self-determination right to have its independent. Indeed, historically The Dutch colonialized Indonesia; meanwhile East Timor was colonialized by the Portugal. Therefore, the creation of UNAMET initiated by the United Nations to give the right to the people in East Timor for referendum whether they choose to be independent or still be apart of Indonesia. This paper will try to prove that UNAMET was not promoted the right to self-determination for people in East Timor for several reasons. Firstly, the peace keeping forces of the UN in East Timor were led by Australia, which had a special interest to East Timor regarding the East Timor Gap Project. Secondly, UNAMET staff proved to be partial in supporting the pro-independence and intimidate the people in society who supported the integration with Indonesia by attacking the members of society who flew the Indonesian flag. Thirdly, the United Nations proved they were only there as a means to protect the US and Australian interests by postponing the referendum through the United Nations Security Council, which created more instability among the people in East Timor.